Relationship between dietary selenium intake and serum thyroid function measures in U.S. adults: Data from NHANES 2007–2012 - Liu, Fang; Wang, Kai; Nie, Jiaqi; Feng, Qianqian; Li, Xiaosong; Yang, Yichi; Deng, Ming-Gang; Zhou, Huanhuan; Wang, Suqing (Frontiers in Nutrition, 2022)
Although numerous studies have explored the relationship between selenium intake and thyroid diseases, few epidemiological studies have investigated the association between selenium intake and thyroid hormones. Therefore, we conducted this analysis to investigate the association between dietary selenium intake and thyroid hormones. Our sample included 5575 adults (age ≥20) years from the National Health and Nutrition Examination Survey (NHANES) 2007-2012. Thyroid hormones, including total triiodothyronine (T3), total thyroxine (T4), free T3 (FT3), free T4 (FT4), and thyroid-stimulating hormone (TSH), were detected. Multivariable linear regression models showed that log10-transformed selenium intake (LogSe) was negatively correlated with TT4 (β= -0.383, 95% CI: -0.695, -0.070) and TT4/TT3 (β=-0.003, 95% CI: -0.006, -0.0004) in U.S. adults. Besides, additional stratified analyses by sex demonstrated that LogSe was negatively associated with TT4 (β= -0.007, 95% CI: -0.013, -0.001) and TT4/TT3 (β= -0.664, 95% CI: -1.182, -0.146) and positively associated with FT4/TT4 (β= 0.031, 95% CI: 0.004, 0.059) in male adults. Meanwhile, subgroup analysis by iodine status showed that LogSe was negatively associated with TT4 (β= -0.006, 95% CI: -0.011, -0.002), FT4/FT3 (β= -0.011, 95% CI: -0.023, -0.00002) and TT4/TT3 (β= -0.456, 95% CI: -0.886, -0.026) in iodine sufficiency but not in iodine deficiency adults. Our results demonstrated that the increased dietary selenium intake was negatively correlated with TT4 and TT4/TT3 in U.S. adults. Furthermore, the association between dietary selenium intake and thyroid hormones was more pronounced in males and iodine sufficiency adults.